1997
DOI: 10.3758/bf03211912
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cognitive and sensorimotor maps of visual space

Abstract: Studies of saccadic suppression and induced motion have suggested separate representations of visual space for perception and visually guided behavior. Because these methods required stimulus motion, subjects might have confounded motion and position. We separated cognitive and sensorimotor maps without motion of target, background, or eye, with an "induced Roelofs effect": a target inside an off-center frame appears biased opposite the direction of the frame. A frame displayed to the left of a subject's cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
275
5
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 375 publications
(322 citation statements)
references
References 38 publications
41
275
5
1
Order By: Relevance
“…The first two conditions in our study test this prediction and essentially replicate Bridgeman et al [2], but in a setting more typical of large-screen collaborative environments.…”
Section: The Induced Roelofs Effectsupporting
confidence: 65%
See 4 more Smart Citations
“…The first two conditions in our study test this prediction and essentially replicate Bridgeman et al [2], but in a setting more typical of large-screen collaborative environments.…”
Section: The Induced Roelofs Effectsupporting
confidence: 65%
“…The first step in our research was a pilot study that successfully reproduced the previous laboratory findings of Bridgeman et al [2], but in a setting more representative of collaborative and immersive display environments. This demonstrated that a displaced frame surrounding a target will cause some participants to make systematic errors in verbally reported location judgments but not in pointing without visual feedback (also known as "open-loop" pointing in experimental psychology).…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations